New Trends in Table Olive Fermentation, 2nd Edition - Bautista-Gallego, Joaquín; Noé Arroyo-López, Francisco; Bordons, Albert; Jiménez-Díaz, Rufino (Frontiers Media SA, 2020)
Table olives are a traditional fermented vegetable with many centuries of history, particularly in the Mediterranean basin, where this food has had a great influence on the culture and diet of many countries. Moreover, this fermented food is prepared with fruits obtained from cultivated Olea eoropaea subsp. europaea var. europea trees and has been expanded for many countries all over the world. At present, the table olive is one of the major fermented vegetables, with an overall production above 2,500,000 tons/year. Thus, the table olive industry is increasingly demanding new biotechnological approaches, sensory characteristics and differentiation of the products. So scientists have to focus on solving problems and providing new tools in this fermented food process. In recent years, there is an increased interest in different nutritional and microbial aspects related to table olives. During the last five years, new fields have been implemented or developed, such us new probiotic strains to produce an enriched product, study of pathogen survival, NaCl content reduction, microbial resistant to stress conditions, microbial biofilms, predictive microbiology, use of NGS and metagenomics, use of bioactive compounds derived from table olive processing and the treatment of effluents generated during olive processing. The diversity of research displayed in this Research Topic demonstrates the important potential of this product and its impact on the fermented vegetables economy.